1999
DOI: 10.1088/0953-2048/12/9/201
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure synthesis, crystal growth, phase diagrams, structural and magnetic properties of Y2Ba4CunO2n+x, HgBa2Can-1CunO2n+2+deltaand quasi-one-dimensional cuprates

Abstract: In this paper we present a review of high-gas-pressure single crystal growth studies of YBa2Cu4O8 and Y2Ba4Cu7O15-x performed in oxygen pressure up to 3000 bar and Hg1-xMxBa2Can-1CunO2n+2+ (M = Pb, Re; n = 1-7) compounds in argon pressure up 11 000 bar at temperature up to 1200 °C. Chain compounds A1-xCuO2 (A = Sr, Ca, Ba) have been synthesized at high oxygen pressure up to 2000 bar. High-pressure phase diagram studies of the investigated systems are also discussed. Structure analyses of Y2Ba4CunO2n+x (n = 6-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 107 publications
1
26
0
1
Order By: Relevance
“…Figure 2a shows the (0<h<5, 0<k<4) portion of reciprocal space, where there is strong evidence of diffuse streaks running along the a* and b* directions and crossing all the Bragg peaks. Our high energy XRD data confirm the formation of O i stripes intercalated between the CuO 2 planes, both in the (100) and (010) directions 26 . The spatial distribution of the intensity of the streaks was obtained by SµXRD (see Methods).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Figure 2a shows the (0<h<5, 0<k<4) portion of reciprocal space, where there is strong evidence of diffuse streaks running along the a* and b* directions and crossing all the Bragg peaks. Our high energy XRD data confirm the formation of O i stripes intercalated between the CuO 2 planes, both in the (100) and (010) directions 26 . The spatial distribution of the intensity of the streaks was obtained by SµXRD (see Methods).…”
supporting
confidence: 70%
“…Here we report micro X-ray diffraction imaging of the spatial distribution of both the charge-density-wave 'puddles' (domains with only a few wavelengths) and quenched disorder in HgBa 2 CuO 4+y , the single layer cuprate with the highest T c , 95 kelvin [26][27][28] . We found that the charge-density-wave puddles, like the steam bubbles in boiling water, have a fat-tailed size distribution that is typical of selforganization near a critical point 19 .…”
mentioning
confidence: 99%
“…Details of the sample preparation for YBa 2 Cu 4 O 8 can be found elsewhere [16]. All crystals used in the present study were taken from one batch.…”
mentioning
confidence: 99%
“…The YBa 2 Cu 4 O 8 single crystal investigated in this work was fabricated by a highpressure synthesis method described in detail elsewhere [7,8]. The volume of the nearly rectangular shaped sample is estimated to be 3.9 · 10 −4 cm 3 .…”
Section: Experiments and Analysismentioning
confidence: 99%